CONTEXTUALIZED LEARNING MODULES IN BRIDGING STUDENTS’ LEARNING GAPS IN CALCULUS WITH ANALYTIC GEOMETRY THROUGH INDEPENDENT LEARNING - Madrazo, Anthony Loria; Dio, Ryan Villareas (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
The transition of the educational system in the Philippines vastly affects basic and higher education.Â A mismatch of pre-requisite Mathematics learning competencies from the basic education level occurred when the student reached higher education.Â This descriptive-developmental method of the study utilized the developed contextualized learning modules for the bridging course on the identified learning gaps in Calculus with Analytic Geometry for the Bachelor of Secondary Education (BSEd) major in Mathematics. Real-world concepts and situations featuring the Province of Sorsogon, Philippines were integrated into the learning modules while promoting independent learning. The content, format, presentations and organizations, accuracy, and up-to-datedness of information of the learning modules passed the evaluation of 13 experts (Mathematics Professors) from the different Higher Education Institutions (HEIs) in the Bicol Region, Philippines. Also, the 18 student participants were very much satisfied with the utilization of the learning modules that bridged their learning gaps in the conic section through independent learning.